Streptomyces lavendulae Protease Inhibitor: Purification, Gene Overexpression, and 3-Dimensional Structure - D. E. El-Hadedy; El-Sayed E. Mostafa; Moataza M. Saad (Journal of Chemistry)
Protease inhibitors trypsin (STI1, Streptomyces trypsin inhibitor 1) has been identified, purified by ammonium sulfate precipitation and Sephadex G-100 gel filtration. SDS-PAGE of protease inhibitor showed molecular weight of approximately 10 KDa. PCR product (~1615 bp) of sti1 gene was cloned in expression vector pACYC177/ET3d and transformed in Escherichia coli JM109. Protease inhibitors trypsin was purified and used as antivirus against Coxsackievirus B3 (CVB3). CVB3 is one of the major causative agents of chronic, subacute, acute, and fulminant myocarditis as well as pancreatitis and aseptic meningitis. It has been reported that more than 50% of human myocarditis is associated with CVB3 infection.